What measures of culture are important for the functioning of the economy - V. N. Krasnov (Путеводитель предпринимателя, 2020)
The paper examines the interpretation of individualism-collectivism as the key culture dimensions, which have the most significant impact on the economy. The author explains the view, according to which individualism and collectivism are not monosemantic categories. They represent a form ofchanging content, and reflect the fundamental differences in the nature ofhuman behavior. The latter are connected with the inclinationfor opportunism and deviation of moral norms.